Carbon-loaded silver catalyst and preparation method and application thereof

By regulating the interaction between Ag and carbon and limiting Ag reconstruction, a carbon-supported silver catalyst was prepared, which solved the problem of low activity and stability of Ag-based catalysts, and achieved an efficient CO2 reduction process, with high current density and long-term stability.

CN119900045AActive Publication Date: 2025-04-29TIANJIN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311401277.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

The existing Ag-based catalysts have low reactivity and stability during CO2 reduction to CO, and have insufficient current density and are prone to loss of activity during electrocatalysis.

Method used

Through impregnation and further calcination, the interaction between Ag and carbon (C) is adjusted, the reconstruction of Ag is limited, and a carbon-supported silver catalyst is formed, which promotes electron transfer and adsorption and stability of the intermediate *COO-.

Benefits of technology

The catalytic performance of high current density, high selectivity and high stability in electrocatalytic CO2 reduction was achieved. The Faraday efficiency of CO was maintained above 90%, and a long-term stability of 600h was achieved at a current density of 500mA/cm2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900045A_ABST
    Figure CN119900045A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-loaded silver catalyst as well as a preparation method and application thereof, silver nitrate and carbon are impregnated at room temperature, then the obtained precursor is ground into powder at room temperature, and the carbon-loaded silver catalyst is obtained after roasting. The carbon-loaded silver catalyst can be applied to preparation of carbon monoxide by electrocatalytic reduction of carbon dioxide. According to the invention, the interaction between silver and carbon is modulated mainly by regulating and controlling the calcination temperature in the preparation process. Due to the formation of carbon-loaded silver with a carbon semi-coated structure, electron transfer in the reaction process is enhanced, and adsorption and stability of an intermediate * COO <-> are enhanced; in addition, the interaction between silver and carbon is enhanced, so that the reconstruction of silver in the reaction process is limited, and the stability under high current is realized. When applied to preparation of carbon monoxide by reduction of carbon dioxide, the catalyst shows excellent performance of preparation of carbon monoxide by reduction of carbon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic carbon dioxide reduction electrodes, and in particular, relates to a method for preparing a carbon-supported transition metal catalyst and its application in promoting the generation of carbon monoxide products. Background Art

[0002] In recent years, with the excessive use of fossil fuels, carbon dioxide (CO 2 ) emissions are increasing year by year, and the resulting greenhouse effect is becoming increasingly serious. 2 The conversion of carbon monoxide (CO) into valuable carbon-based products is a promising method to achieve carbon neutrality. Among the numerous reduction products, carbon monoxide (CO) has attracted extensive attention as a basic chemical raw material. 2 Reduction to CO is thermodynamically feasible, but is limited by the CO 2 The difficulty in adsorbing electrons, HER competitive reactions, and catalyst reconstruction during the reaction process still pose great challenges to the further development of CO catalysts with high activity and high stability.

[0003] To date, researchers have explored a range of homogeneous and heterogeneous electrocatalysts for CO 2 Among these catalysts, silver (Ag)-based catalysts have shown excellent catalytic performance for CO and have received widespread attention. However, their activity and stability need to be further improved. At present, people have tried various methods to further improve the CO 2 RR performance, such as particle size regulation (Salehi-Khojin A, Jhong HRM, Rosen BA, et al. Nanoparticle silver catalysts that show enhanced activity for carbondioxide electrolysis [J]. The Journal of Physical Chemistry C, 2013, 117 (4): 1627-1632), surface modification (Li P, Bi J, Liu J, et al. In situ dual doping for constructing efficient CO 2-to-methanol electrocatalysts[J].Nature Communications, 2022,13(1):1-9), heteroatom doping, etc. (Zhang Z, Wen G, Luo D, et al. "Two ships in a bottle" design for Zn-Ag-O catalyst enabling selective and long-lasting CO 2 Liu et al. improved the adsorption of *COOH by doping Ag with heteroatom Sn to establish a strong atomic local electric field. The obtained Ag / Sn catalyst maintained almost unchanged CO Faraday efficiency (CO FE of about 100%) for more than 20 hours and achieved a high current density of up to 200 mA / cm 2 The high current density (Cai C, Liu B, Liu K, et al. Heteroatoms induce localization of the electric field and promote a wide potential-window selectivity towards CO in the CO 2 electroreduction[J].Angewandte Chemie International Edition, 2022, 61(44):e202212640). Zhao et al. introduced Cr 2 O 3 carrier, found Ag-Cr 2 O 3 The formation of interfacial sites effectively stabilizes CO 2 ·- / *COOH intermediate, in the electrocatalytic reduction of CO 2 Excellent activity and stability were achieved in the process of converting to CO (Fu HQ, Liu J, Bedford NM, et al. Synergistic Cr 2 O 3 @Ag heterostructureenhanced electrocatalytic CO 2rduction to CO[J]. Advanced Materials, 2022:2202854).

[0004] It is not difficult to find that although the corresponding research has made some progress, in most studies, the current density is still ≤300mA / cm -2 Moreover, during the electrocatalytic process, the reconstruction of Ag often leads to a gradual loss of activity and stability. Therefore, it remains a challenge to develop Ag-based catalysts that can simultaneously achieve high current density, high selectivity, and high stability for CO generation. Summary of the invention

[0005] The present invention aims to solve the technical problem of low reaction activity and stability of Ag-based catalysts, and provides a carbon-supported silver catalyst and its preparation method and application. By impregnation and further calcination, the interaction between Ag and carbon (C) is adjusted by high-temperature calcination, so as to promote the electron transfer in the reaction process and strengthen the intermediate *COO - adsorption and stabilization; and limit the reconstruction of silver during the reaction, making it 2 It exhibits excellent reactivity and stability in the reduction of CO and can be used in the electrocatalytic CO 2 Application in CO reduction.

[0006] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:

[0007] A carbon-supported silver catalyst and a preparation method thereof, wherein Ag particles are uniformly supported on the carbon surface, wherein the particle size of the Ag particles is 4-75 nm, preferably 4-22 nm, and the steps are as follows:

[0008] Step 1, adding carbon powder to an aqueous solution of silver nitrate and dispersing the mixture, collecting the product by centrifugation and drying the product, wherein the amount of carbon powder added is 50-100% of the mass of the silver nitrate;

[0009] Step 2, under the protection of an inert atmosphere, heating the product obtained in step 1 from room temperature 20-25 degrees Celsius to 400-800°C at a rate of 5-10 degrees Celsius per minute and maintaining for 1-2 hours, and naturally cooling to room temperature to obtain a carbon-supported silver catalyst.

[0010] In the technical solution of the present invention, the carbon powder (ie, C carbon) is Cabot VXC 72 or Super P.

[0011] In the technical solution of the present invention, the inert protective gas is nitrogen, helium or argon.

[0012] In the technical solution of the present invention, the added amount of carbon powder is 60-100% of the mass of silver nitrate.

[0013] In the technical solution of the present invention, carbon powder is added to the aqueous solution of silver nitrate and dispersed to fully impregnate carbon and silver, and ultrasonic or stirring treatment is selected for 10-15 hours, preferably 10-12 hours.

[0014] The carbon-supported silver catalyst of the present invention is used for electrocatalytic CO 2 Application in CO reduction.

[0015] In the application, the carbon-supported silver catalyst is sprayed onto a gas diffusion electrode (such as carbon paper) as a working electrode, and IrO 2 As the counter electrode, it is assembled into an electrochemical cell and CO is introduced into the electrolyte. 2 , the electrolyte is 0.05-0.005 mol / L Cs 2 CO 3 Aqueous solution, electricity is passed through to carry out electrocatalytic reaction.

[0016] In the application, 0.5-2 mg of carbon-supported silver catalyst is sprayed per square centimeter of gas diffusion electrode.

[0017] The silver-carbon catalyst of the present invention obtains silver-carbon with a more stable structure by adjusting the calcination temperature. The introduction of the C carrier improves the dispersibility of the Ag particles, so that the Ag particles with a particle size of 4-75nm are uniformly loaded on the C carrier. At the same time, the enhanced interaction between Ag and C effectively avoids the agglomeration of Ag particles, forms an electron-rich interface site, and promotes the *COO - The formation and stabilization of CO 2 Reduction reactivity and stability.

[0018] The preparation method of the silver-carbon catalyst of the present invention uses commonly used conductive carbon black (Cabot VXC 72 or Super P) as a C source and silver nitrate as a silver source, and obtains the silver-carbon catalyst by impregnation and further calcination. The raw materials required in the preparation process are simple, the preparation method is simple and easy, batch preparation can be realized, and it has certain industrialization prospects.

[0019] The silver-carbon catalyst of the present invention is used for electrocatalysis of CO 2 The enhanced interaction between Ag and C strengthens the electron transfer during the reaction. On the other hand, the highly localized electron density at the silver-carbon interface promotes the reduction of *COO - The formation and stability of Ag / C enhances the reaction activity; at the same time, the semi-encapsulated Ag / C catalyst enhances the interaction between Ag and C, limiting the reconstruction of Ag during the reaction. 2The Faraday efficiency of CO is above 90% within the current density range of 500 mA / cm 2 At a current density of 1.3 Å, a long-term stability of up to 600 h was achieved. 2 Excellent performance in CO production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The Ag-C obtained in Examples 1, 3, and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 Transmission electron microscope photos and particle size statistics.

[0021] Figure 2 The Ag-C obtained in Examples 1, 3, and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 Transmission electron microscope photograph of .

[0022] Figure 3 The Ag-C obtained in Examples 1, 3, and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 XRD diffraction spectrum.

[0023] Figure 4 The Ag-C obtained in Example 2 VXC 72 Transmission electron microscopy image of the catalyst.

[0024] Figure 5 The Ag / C prepared in Example 5 Super P Transmission electron microscope photograph and particle size statistics of the catalyst.

[0025] Figure 6 The Ag-C obtained in Examples 1, 3, and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 Under the conditions of the example, CO 2 Restore performance test chart.

[0026] Figure 7 The Ag-C obtained in Examples 1, 3, and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 Under the conditions of the example, CO 2 Cell voltage graph and energy efficiency graph for reduction performance test.

[0027] Figure 8 The Ag-C obtained in Examples 1, 3, and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72Under the conditions of the example, CO 2 Reduction stability test chart.

[0028] Fig. 9 The Ag-C obtained in Examples 1, 3, and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 Under the conditions of the example, CO 2 Transmission electron microscope photos and particle size statistics after reduction stability test.

[0029] Fig.10 The Ag-C obtained in the examples 1, 3 and 4 is VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 In-situ infrared test image. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below through specific examples. The following examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.

[0031] Example 1—Ag-C VXC 72 Preparation of silver-carbon catalysts (i.e., silver particles simply dispersed on the carbon surface)

[0032] (1) Accurately weigh 0.5 g AgNO 3 Add to 50 mL of deionized water and stir to dissolve to obtain AgNO 3 Then, 0.3 g of C powder (Cabot VXC 72) was added and ultrasonicated for 1 h to obtain Ag + -C VXC 72 suspension; the resulting suspension was stirred (300 revolutions per minute) for 12 hours, and then the product was collected by centrifugation and dried at 60°C.

[0033] (2) The obtained powder was placed in a tube furnace, oxygen was removed by nitrogen, and then the nitrogen flow rate was maintained at 80 standard cubic centimeters per minute (sccm). 2 The inert protective gas atmosphere was maintained by heating from room temperature (20-25 degrees Celsius) to 400 degrees Celsius at a rate of 10 degrees Celsius per minute and maintained for 2 hours. After cooling naturally to room temperature, Ag-C VXC 72 .

[0034] from Figure 1 It can be seen from a that the Ag-C prepared in Example 1 VXC 72 Transmission electron microscope pictures of Ag-C VXC 72 In the example, Ag particles are uniformly loaded on the C surface. Figure 1 As can be seen from b, the Ag-C prepared in Example 1VXC 72 The particle size distribution of Ag-C VXC 72 The particle size of Ag is distributed in the range of 4-18nm. Figure 2 It can be seen from a that the Ag-C prepared in Example 1 VXC 72 Transmission electron microscope pictures of Ag-C VXC 72 In the case of Ag, Ag is dispersed on the C surface. Figure 3 It can be seen that the Ag-C prepared in Example 1 VXC 72 Except for the diffraction peak belonging to C at about 20° (2Theta), the other diffraction peaks completely match the standard card of Ag (PDF#04-0738), indicating that Ag with good crystallinity was obtained.

[0035] Example 2—Ag-C VXC 72 Preparation

[0036] The only difference from Example 1 is that the obtained powder is heated in a tube furnace at 80 sccm of N 2 The air flow was heated to 400℃ and maintained for 1h. After cooling to room temperature, Ag-C VXC 72 .

[0037] Figure 4 The Ag / C prepared in Example 2 VXC 72 Transmission electron microscope image of Figure 4 It can be seen that the Ag particles are uniformly loaded on the C surface.

[0038] Example 3 - Ag / C VXC 72 Preparation of (i.e., semi-coated silver-carbon catalyst in which silver particles are partially coated with carbon)

[0039] The only difference from Example 1 is that the obtained powder is heated in a tube furnace at 80 sccm of N 2 The air flow was heated to 600℃ and maintained for 2h. After cooling to room temperature, Ag / C VXC 72 .

[0040] from Figure 1 As can be seen from c, the Ag / C prepared in Example 3 VXC 72 The transmission electron microscopy photograph of the Ag / C prepared in Example 3 VXC 72 In the example, Ag particles are uniformly loaded on the C surface. Figure 1 The Ag / C prepared in Example 3 can be VXC 72 The particle size distribution diagram of the Ag / C prepared in Example 3 VXC 72 In the figure, we can see that the particle size of Ag is distributed in the range of 4-22nm. Figure 2 As can be seen from b, the Ag / C prepared in Example 3 VXC 72The transmission electron microscopy photograph of the Ag / C prepared in Example 3 VXC 72 In the example, Ag is partially covered by C, forming a semi-covered silver-carbon structure. Figure 3 It can be seen that the Ag-C prepared in Example 3 VXC 72 Except for the diffraction peak belonging to C at about 20° (2Theta), the other diffraction peaks completely match the standard card of Ag (PDF#04-0738), indicating that Ag with good crystallinity was obtained.

[0041] Example 4—Ag@C VXC 72 Preparation of a fully coated silver-carbon catalyst in which silver particles are completely coated with carbon

[0042] The only difference from Example 1 is that the obtained powder is heated in a tube furnace at 80 sccm of N 2 The air flow was heated to 800℃ and maintained for 2h. After cooling to room temperature, Ag@C was obtained. VXC 72 .

[0043] from Figure 1 As can be seen from the figure, the Ag@C prepared in Example 4 VXC 72 Transmission electron microscopy photograph of the Ag@C prepared in Example 4 VXC 72 In the example, Ag particles are uniformly loaded on the C surface. Figure 1 As can be seen from the figure, the Ag / C prepared in Example 4 VXC 72 The particle size distribution diagram of Ag@C prepared in Example 4 VXC 72 The particle size of Ag is distributed in the range of 35-75nm. Figure 2 As can be seen from c, the Ag@C prepared in Example 4 VXC 72 Transmission electron microscopy photograph of the Ag@C prepared in Example 4 VXC 72 In the case of Ag, C is completely covered to form a fully covered silver-carbon structure. Figure 3 It can be seen that the Ag@C prepared in Example 4 VXC 72 Except for the diffraction peak belonging to C at about 20° (2Theta), the other diffraction peaks completely match the standard card of Ag (PDF#04-0738), indicating that Ag with good crystallinity was obtained.

[0044] Example 5—Ag / C Super P Preparation

[0045] The only difference from Example 3 is that Super P is used instead of Cabot VXC 72.

[0046] Figure 5 The Ag / C prepared in Example 5 Super P Transmission electron microscope photograph of Figure 5It can be seen that the Ag particles are uniformly loaded on the C surface, and the particle size distribution of Ag is 8-22nm.

[0047] Example 6—Ag / C VXC 72 Preparation

[0048] The difference from Example 1 is that in step (1), AgNO 3 The amount of addition is 0.3 g, and the calcination holding temperature in step (2) is 600° C. and the time is 1 h.

[0049] Example 7—Electrocatalytic CO 2

[0050] The catalysts prepared in Examples 1-6 were electrocatalyzed to 2 Restore performance test.

[0051] The catalyst prepared in the above embodiment was drop-coated on a glassy carbon electrode as a working electrode (0.5-2 mg of silver-carbon catalyst, i.e., the catalyst prepared in the embodiment of the present invention, was drop-coated per square centimeter of the glassy carbon electrode). 2 As the counter electrode, it is assembled into an electrochemical cell to form a two-electrode system; CO is continuously introduced into the electrochemical cell. 2 , for electrocatalytic CO 2 Reduction performance test and electrode stability test. The electrolyte is 0.05 mol / L Cs 2 CO 3 Aqueous solution, working electrode area 4cm 2 The gas phase product was detected by gas chromatography, and the liquid phase product was detected by liquid chromatography and nuclear magnetic resonance quantitative method. 0.5 mg of the catalyst prepared in Example 1-6 was subjected to an applied current density of 500 mA / cm 2 The CO product selectivity under the conditions is shown in the following table.

[0052] CO FE (%) Example 1 97 Example 2 97 Example 3 99 Example 4 92 Example 5 89 Example 6 98

[0053] Using 2 mg of the catalyst prepared in Examples 1, 3 and 4, the catalytic activity was tested at different current densities. The product distribution is as follows: Figure 6 As shown. Figure 6 It can be seen that Ag / C VXC 72 Performance is much better than Ag-C in a wider current density range VXC 72 and Ag@C VXC 72 : Figure 6 Where a is the Ag-C prepared in Example 1 VXC 72 CO 2 Reduction performance, experimental results show that the Ag-C prepared in Example 1 VXC 72 Catalyst, 100-700mA / cm 2At current densities of 2.5 and 1.5 W, the CO selectivity is maintained above 90%. Figure 6 b is the Ag / C prepared in Example 3 VXC 72 CO 2 Reduction performance, experimental results show that the Ag-C prepared in Example 3 VXC 72 Catalyst, at 100-1100mA / cm 2 At current densities of 2.5 and 1.5 W, the CO selectivity is maintained above 90%. Figure 6 Where c is Ag@C prepared in Example 4 VXC 72 CO 2 Reduction performance, experimental results show that the Ag@C prepared in Example 4 VXC 72 Catalyst, 100-500mA / cm 2 At current densities of 2.5 and 1.5 W, the CO selectivity is maintained above 90%.

[0054] Figure 7 The Ag-C obtained in Examples 1, 3, and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 Under the conditions of the example, CO 2 Cell voltage diagram and energy efficiency diagram of reduction performance test. a is the Ag-C prepared in Examples 1, 3, and 4. VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 At 100-1500mA / cm 2 The cell voltage at the current density is Figure 7 In a, it can be seen that in the entire test range, the Ag / C obtained in Example 3 VXC 72 The cell voltage is better than that of the Ag-C VXC 72 and the Ag@C obtained in Example 4 VXC 72 b is the Ag-C prepared in Examples 1, 3, and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 At 100-1500mA / cm 2 Energy efficiency at current density, from Figure 7 In b, it can be seen that in the entire test range, the Ag / C VXC 72 The energy efficiency of the Ag-C VXC 72 and the Ag@C obtained in Example 4 VXC 72 .

[0055] Figure 8 The Ag-C prepared in Examples 1, 3 and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72At 500mA / cm 2 CO at current density 2 Restore the stability diagram. Figure 8 As can be seen from a and b in the figure, in the 100h stability test, Ag-C VXC 72 and Ag@C VXC 72 The cell voltage changed significantly with time and the FE of CO decreased significantly. VXC 72 During the entire test process, the cell voltage and the FE of CO remained basically unchanged, which was much better than that of the Ag-C obtained in Example 1. VXC 72 and the Ag@C obtained in Example 3 VXC 72 When the electrolyte is further reduced to 0.005 mol / L, the Ag / C VXC 72 The catalyst was tested for stability up to 600 hours, and the cell voltage remained basically unchanged during the entire test, and the FE of CO was maintained above 95%. Figure 8 As shown in c.

[0056] Fig. 9 The Ag-C prepared in Examples 1, 3 and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 At 500mA / cm 2 Transmission electron microscope photos and particle size statistics after stability testing at current density. Fig. 9 In a, we can see that Ag-C VXC 72 The Ag particles in the catalyst showed obvious agglomeration, and the particle size increased significantly compared with that before the reaction. Figure 1 b and Fig. 9 b. Ag / C VXC 72 and Ag@C VXC 72 After stability testing, the particle size remained essentially unchanged, see Figure 1 cf and Fig. 9 cf in, indicating Ag / C VXC 72 and Ag@C VXC 72 Has good stability.

[0057] Ag / C in the embodiment of the present invention VXC 72 The formation of the semi-encapsulated structure effectively improves the CO 2 Reduction activity and stability, such as Figure 6 , as shown in 7. Fig.10 As shown, the Ag-C prepared in Examples 1, 3, and 4 VXC 72 、Ag / C VXC 72 and Ag@C VXC 72 In-situ infrared test diagram, it is found that the Ag-C obtained in Example 1 VXC 72and the Ag@C obtained in Example 4 VXC 72 No *COO detected on the surface - / *COOH absorption peak, see Fig.10 a and c indicate CO 2 RR intermediates in Ag-C VXC 72 and Ag@C VXC 72 The binding on Ag / C VXC 72 Two obvious peaks can be observed, see Fig.10 Middle B, located at 1378cm -1 The peak is attributed to *COO - Symmetrical stretch, and located at 1284cm -1 The other absorption peak is attributed to the C-OH stretching of *COOH. When the applied potential changes from -0.3 to -1.1 V vs. RHE, the Ag / C VXC 72 Surface *COOH and *COO - The peak becomes broad, indicating that *COO - / *High coverage of COOH. Ag / C VXC 72 Surface *COO - / *Formation and stabilization of COOH intermediates in CO 2 The appropriate interaction between Ag and C is conducive to the reduction of *COO - / *COOH is adsorbed on the catalyst surface, which makes the catalyst have higher CO 2 Restore performance.

[0058] It can be seen from the above examples that the carbon-supported silver catalyst of the present invention has an effect on the electrocatalytic reduction of CO 2 It showed good activity and stability to CO. At a current density of 100-1100 mA / cm 2 Under the condition of 500mA / cm 2 Under the condition of , a long-term durability of more than 600 h was achieved, and the cell voltage remained almost unchanged during the entire reaction process, and the FE of CO remained above 95%. The results of in situ ATR-SEIRAS and electrochemical experiments showed that the strong interaction between Ag and C not only promoted electron transfer, but also stabilized the COO - , thereby improving the activity, and also effectively inhibiting the reconstruction of Ag during the electrocatalytic process, thus having high stability.

[0059] According to the content of the present invention, the preparation process can be adjusted to achieve the preparation of the catalyst of the present invention, and after testing, the catalyst exhibits performance substantially consistent with the present invention. The present invention is described above by way of example, and it should be noted that any simple deformation, modification or equivalent replacement that can be made by other technicians in this field without inventive labor falls within the protection scope of the present invention without departing from the core of the present invention.

Claims

1. A carbon-supported silver catalyst, characterized in that Ag particles are uniformly loaded on the carbon surface, and the particle size of the Ag particles is 4-75 nm, according to the following steps: Step 1, adding carbon powder to an aqueous solution of silver nitrate and dispersing the mixture, collecting the product by centrifugation and drying the product, wherein the amount of carbon powder added is 50-100% of the mass of the silver nitrate; Step 2, under the protection of an inert atmosphere, heating the product obtained in step 1 from room temperature 20-25 degrees Celsius to 400-800°C at a rate of 5-10 degrees Celsius per minute and maintaining for 1-2 hours, and naturally cooling to room temperature to obtain a carbon-supported silver catalyst.

2. The carbon-supported silver catalyst according to claim 1, characterized in that The particle size of the Ag particles is 4-22 nm.

3. The carbon-supported silver catalyst according to claim 1 or 2, characterized in that The amount of carbon powder added is 60-100% of the mass of silver nitrate.

4. A method for preparing a carbon-supported silver catalyst, characterized in that: Follow the steps below: Step 1, adding carbon powder to an aqueous solution of silver nitrate and dispersing the mixture, collecting the product by centrifugation and drying the product, wherein the amount of carbon powder added is 50-100% of the mass of the silver nitrate; Step 2, under the protection of an inert atmosphere, heating the product obtained in step 1 from room temperature 20-25 degrees Celsius to 400-800°C at a rate of 5-10 degrees Celsius per minute and maintaining for 1-2 hours, and naturally cooling to room temperature to obtain a carbon-supported silver catalyst.

5. The method for preparing a carbon-supported silver catalyst according to claim 4, characterized in that: The amount of carbon powder added is 60-100% of the mass of silver nitrate.

6. The method for preparing a carbon-supported silver catalyst according to claim 4, characterized in that: The carbon powder is Cabot VXC 72 or Super P.

7. The method for preparing a carbon-supported silver catalyst according to claim 4, characterized in that: The inert protective gas is nitrogen, helium or argon.

8. The method for preparing a carbon-supported silver catalyst according to claim 4, characterized in that: Add carbon powder to the aqueous solution of silver nitrate and disperse it to fully impregnate the carbon and silver. Select ultrasonic or stirring treatment for 10-15 hours, preferably 10-12 hours.

9. Use of the carbon-supported silver catalyst as claimed in any one of claims 1 to 3 in electrocatalytic CO2 reduction to produce CO.

10. The use of the carbon-supported silver catalyst according to claim 9 in electrocatalytic CO2 reduction to produce CO, characterized in that: When applied, the carbon-loaded silver catalyst is sprayed onto a gas diffusion electrode (such as carbon paper) as a working electrode, IrO2 as a counter electrode, assembled into an electrochemical cell, CO2 is introduced into the electrolyte (such as a 0.05-0.005 mol / L Cs2CO3 aqueous solution), and power is turned on for an electrocatalytic reaction. 0.5-2 mg of carbon-loaded silver catalyst is sprayed per square centimeter of the gas diffusion electrode.

Citation Information

Patent Citations

  • Supported silver-carbon catalyst for salt electrolysis and preparation method thereof

    CN101745390A

  • PtAg / C catalyst and preparation method thereof

    CN103586021A

  • Ag / C catalyst and preparation method thereof

    CN108767274A

  • Preparation method of carbon-loaded nano-silver catalyst

    CN110548507A

  • Preparation method of Ag-loaded self-supporting carbon film and application of Ag-loaded self-supporting carbon film as electrocatalytic CO2 reducing gas diffusion electrode

    CN115821306A